Validations of sensory overall acceptability optimizations on response surface methodology through just-about-right technique for coffee-leaf tea at different brewing methods - Fibrianto, Kiki; Bimo, Igoy Arya; Sofa, Atika Muna; Putri, Azalea; Amelia, Devia; Lalilika, Ovirista Rachma; Genbrovit, Irha Putri; Haq, Ahmad Izzul (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Response Surface Methodology (RSM) has been widely employed for optimizing processes. However, the implementation of RSM in sensory studies is still limited. Moreover, most publications implementing RSM on sensory disregarded the validation stage as normally applied for process optimization. In this study, validating sensory overall acceptability with RSM was proposed by the Just-About-Right (JAR) technique. Coffee-leaf tea has great commercial potential as an ethnic beverage with unique sensory attributes but is still underutilized. Optimizing sensory acceptability level by modifying temperature and duration of brewing using the RSM was expected to obtain well-accepted coffee-leaf tea.  Robusta coffee leaf tea is brewed using combined Decoction - V60, French Press, combined French Press - V60, and V60 at 90oC to 100oC for 2 to 10 minutes. Evaluated by 110 untrained panelists, it was observed that the ideal brewing parameters for each technique were 96.6oC for 6.5 minutes for Decoction – V60, 96oC and 6.5 minutes for French Press, 90oC and 2 minutes for French Press - V60, and 90oC and 2 minutes for V60. All optimum brewing conditions based on RSM were successfully validated by overall acceptability on JAR (p-value 0.05). Thus, the JAR technique can enhance the overall sensory acceptability analysis and optimization.